2018
DOI: 10.22478/ufpb.1981-0695.2018v13n1.40637
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmicas e indicadores de comunicação do XVIII Encontro Nacional de Pesquisa em Ciência da Informação: Relatos sobre o GT1 - Estudos Históricos e Epistemológicos da Ciência da Informação

Abstract: O Encontro Nacional de Pesquisa em Ciência da Informação (ENANCIB) é dedicado à comunicação e divulgação da produção científica em Ciência da Informação. Em sua décima oitava edição, o encontro foi organizado em 11 (onze) grupos de trabalho (GTs). Este relato apresenta as dinâmicas de organização e funcionamento do GT1 – Estudos Históricos e Epistemológicos da Ciência da Informação, na décima oitava edição do evento, bem como os indicadores de comunicação, considerando a modalidade, o vínculo institucional e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
1
1
3
Order By: Relevance
“…[59] Another point to be discussed is the association between risk perception and knowledge. In the present study, with each increase of 1 point in the perception of risk, the chance of having knowledge above the average increased by about 1%, contradicting the results of previous Brazilian [60] and Chinese [61] studies, in which the association between these variables was negative. Nevertheless, it should be noted that studies on Middle East Respiratory Syndrome had already indicated a positive association between knowledge and risk perception [62,63] ; and also that it is predicted that the greater the risk perception that the individual has of the pandemic, the more information is sought on how to avoid the disease.…”
Section: N (%)contrasting
confidence: 99%
“…[59] Another point to be discussed is the association between risk perception and knowledge. In the present study, with each increase of 1 point in the perception of risk, the chance of having knowledge above the average increased by about 1%, contradicting the results of previous Brazilian [60] and Chinese [61] studies, in which the association between these variables was negative. Nevertheless, it should be noted that studies on Middle East Respiratory Syndrome had already indicated a positive association between knowledge and risk perception [62,63] ; and also that it is predicted that the greater the risk perception that the individual has of the pandemic, the more information is sought on how to avoid the disease.…”
Section: N (%)contrasting
confidence: 99%
“…These authors defended the idea of librarians and information professionals acting within the parameters proposed by them for IA, because the discussions developed by theoreticians from other areas of knowledge, such as Design and Computer Science, were not able to meet the existing demands related to the structuring of information in digital information environments, paying attention to the requirements of the subareas of Information Organization and Information Retrieval. This is also argued by Oliveira, Vidotti (2012), Souza and Silva (2016). Moreover, authors such as Siqueira (2016) and Alvarez, Brito and Vidotti (2020) consider IA as a scientific discipline within Information Science.…”
Section: Introductionmentioning
confidence: 75%
“…A origem da usabilidade deriva da Ergonomiacampo de estudo da Engenharia e do Design que relaciona o trabalho, a tecnologia e as organizações sociais de forma humanizada como o objetivo de aprimorar as condições de trabalho (SOUZA, 2015).…”
Section: Usabilidadeunclassified